Need analysis for the development of an augmented reality-based learning module on isometric transformation for Form 2 students in Malaysia - Osman, Noorul Shuhadah; Mohd Ayub, Ahmad Fauzi; Zulkifli, Nurul Nadwa; Mahat, Jazihan (Universiti Putra Malaysia, 2024)
Augmented Reality (AR) has emerged as a promising educational technology, providing immersive and interactive learning experiences that boost student engagement and enable pupils to visualise. Isometric Transformations, which include translations, reflections, and rotations, are fundamental yet challenging topics in the Malaysian Form 2 mathematics curriculum. Traditional teaching methods often fall short of helping students visualize and understand these transformations, leading to significant learning gaps and decreased motivation. The interactive and immersive nature of AR could potentially bridge this gap by allowing students to visualize transformations in real time, thus enhancing their spatial reasoning, conceptual understanding, and motivation to learn. The purpose of this study is to undertake a detailed need analysis for building a learning module incorporating AR technology centred on Isometric Transformation for Malaysian Form 2 students. This study employs structured interviews with experts. A qualitative approach with a structured interview method involved three experts from three districts in Malaysia. The interview results were analysed by breaking the transcripts into multiple codes using a thematic analysis approach. The findings of this study revealed that the topic of Isometric Transformation, especially the Form 2 syllabus, was the most challenging concept for the students to master. The interviews also revealed that the experts agree that using modules to integrate technological elements, specifically AR, is very helpful in learning this topic. They also suggest that the module design should focus on the notes and activities conducted in class during teaching and learning in the classroom. The findings of the item analysis can help the researcher plan more targeted improvement actions according to the student's needs.